‘What Would Denis Have Done?’ A Critical Reflection Upon 2020’s Rapid and Obligatory Transition to Remote Delivery - Nick James (Bond Law Review)
In 2020, the COVID-19 pandemic forced law schools to rapidly transition to remote delivery of their programs and to place a greater emphasis upon technology-enhanced learning. Those legal academics who were unfamiliar with this method of delivery were obliged to very quickly develop their digital skills to facilitate this transition. The outcomes of this transition were mixed: while most law schools managed to continue to deliver their programs during the pandemic, student feedback about the quality of the remote delivery was not always positive. Nevertheless, the emphasis upon remote delivery and technology-enhanced learning is likely to continue and even increase in the coming years. In this paper I interrogate the assumption that the rapid and obligatory transition to remote delivery that took place because of the pandemic will form a stable basis for further development of digital skills by legal academics. Drawing upon the notion of academic resistance as well as the well-known distinctions between surface and deep approaches to learning and intrinsic and extrinsic student motivation, I argue that the impact of the rapid and obligatory transition to remote delivery upon academic motivation, morale, and freedom exposes law schools to the risk that, without mindful intervention, the quality of technology-enhanced learning in law schools will be lower than optimal.